2013
DOI: 10.1007/s00417-013-2273-z
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal pupillography identifies retinal dysfunction in early age-related macular degeneration

Abstract: The mfPOP responses of early AMD eyes showed significant abnormality in response amplitudes and peak time. The ROC AUCs of 95 % suggest that mfPOP is a sensitive tool for detecting early abnormalities in AMD and longitudinal studies measuring progression of retinal dysfunction are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…24 Although perimetry is often used in glaucoma, our mfPOP results on early stage diabetic retinopathy and age-related macular degeneration have also been encouraging, where response delays seem to play a role. 25,37 Overall mfPOP may prove to be useful for several clinical diagnostic problems.…”
Section: Discussionmentioning
confidence: 99%
“…24 Although perimetry is often used in glaucoma, our mfPOP results on early stage diabetic retinopathy and age-related macular degeneration have also been encouraging, where response delays seem to play a role. 25,37 Overall mfPOP may prove to be useful for several clinical diagnostic problems.…”
Section: Discussionmentioning
confidence: 99%
“…Those methods have been demonstrated to have diagnostic value in glaucoma, [14][15][16] early-stage diabetic retinopathy, 17 and age-related macular degeneration. [18][19][20] Aside from the 60 degree-wide stimuli used in most of those studies, mfPOP stimuli for the central retina have also been demonstrated. 18,20,21 Our original stimuli tested 24 regions/field.…”
Section: Introductionmentioning
confidence: 99%
“…Although a visual function deficit in AMD participants was found using the PLR, Brozou et al (2009) focused on the pupil constriction amplitude and velocity, thus only considering the outer (rod and cone) retina driven pupil response. In two separate studies, Sabeti et al (2013;2011) use multifocal pupillography (mfPOP) to assess local retinal function in persons with early AMD (Sabeti et al 2013) and exudative AMD (Sabeti et al 2011) compared to age-matched controls. Mean constriction amplitudes and time to peak delays in AMD participants were decreased; however, mfPOP only assesses the outer retina.…”
Section: : Pupil Light Reflexmentioning
confidence: 99%
“…In AMD, the PLR has been used as a measure of outer retinal function (Asakawa, Ishikawa, Ichibe & Shimizu 2014;Brozou et al 2009;Nakayama, Nowak, Ishikawa, Asakawa & Ichibe 2014;Rosli et al 2012;Sabeti et al 2013;Sabeti et al 2011) and demonstrates a longer latency to constriction and reduction in maximum pupil constriction amplitude. However, these studies were not designed to measure ipRGC function in AMD.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation